Diversité Des Espèces Herbacées Et Lianescentes De La Forêt Classée Du Haut-Sassandra (Centre-Ouest, Côte d’Ivoire) Après Plusieurs Années D’exploitation Forestière - Théodore, Etien Dibié; Aimé, Vroh Bi Tra; Yves, Adou Yao Constant; Edouard, N’Guessan Kouakou (European Scientific Journal, ESJ, 2018)
Natural and anthropogenic disturbances affect forest integrity and floristic composition. The resulting secondary habitats is characterised by liana and herb species which modified the forest physiognomy. To elucidate the floristic characteristics of these secondary forests, the present study was carried out after logging operations in the the Haut-Sassandra protected Forest. The inventory has been realised in 18 individual one ha in three level of logging operation. A total of 445 species have been identified. Floristics parameters vary according to the time after logging operation: from 255 in the south sector, 296 species in the center sector, 271 species in the north sector, 15 years after logging. The family diversity is between 56 and 62 with a predominance of Rubiaceae. Phytogeographic-types are characterized by Guinean-Congolese species (71,2 %), and species endemic to SavannahForest transition zone (14,6 %). The presence of herb and liana species which are pioneer and heliophile, could generate a micro climate favorable to the recovery of other forest plant species.